Pengaruh PW, KWL, and DRTA Terhadap Hasil Belajar Rekognisi dan Recall Matapelajaran Sejarah Indonesia di SMA - Susanto Yunus Alfian (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2019)
This research explores the effects of three instructional methods (Picture Walk, Know-Want To Learn, and Directed Reading Thinking Activity) on the students recognition and recall of historical texts. The subjects were 247 tenth graders of SMA Negeri 1 Sumberpucung. Static-group comparison design was employed that examined 3 treatments: picture walk group, know-want to learn group, and Directed Reading Thinking Activity group. To evaluate the treatment effects, MANOVA was conducted on two measures (recognition and recall tests). Results indicated that PW, KWL, and DRTA yield statistically significant effects on recognition and recall tests. Using post hoc analysis, DRTA is better than the two other methods.